Phytochemical Screening and Anti-nociceptive Properties of the Ethanolic Leaf Extract of Trema Cannabina Lour - Hira Arpona; Dey Shubhra Kanti; Howlader Sariful Islam; Ismet Ara Jahan; Hossain Hemayet; Ahmed Arif (Tabriz University of Medical Sciences, 2013)
Purpose: The present study was designed to investigate the anti-nociceptive activity of ethanolic leaf extract of Trema cannabina Lour (family: Cannabaceae) in experimental animal models. Methods: The anti-nociceptive action was carried out against two types of noxious stimuli, thermal (hot plate and tail immersion tests) and chemical (acetic acid-induced writhing) in mice. Results: Phytochemical analysis of crude extract indicated the presence of reducing sugar, tannins, steroid and alkaloid types of secondary metabolites. Crude extract of T. cannabina (500 mg/kg dose) showed maximum time needed for the response against thermal stimuli (6.79±0.15 seconds) which is comparable to diclofenac sodium (8.26±0.14 seconds) in the hot plate test. Hot tail immersion test also showed similar results as in hot plate test. At the dose of 250 and 500 mg/kg body weight, the extract showed significantly and in a dose-dependent (p<0.001) reduction in acetic acid induced writhing in mice with a maximum effect of 47.56% reduction at 500 mg/kg dose comparable to that of diclofenac sodium (67.07%) at 25 mg/kg. Conclusion: The obtained results tend to suggest the Anti-nociceptive activity of ethanolic leaf extract of Trema cannabina and thus provide the scientific basis for the traditional uses of this plant part as a remedy for pain.